2022
DOI: 10.3390/plants11091197
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nutrient-Specific Response of Maize Hybrids in Relation to Leaf Area Index (LAI) and Remote Sensing

Abstract: Leaf area index (LAI) indicates the leaf area per ground surface area occupied by a crop. Various methods are used to measure LAI, which is unitless and varies according to species and environmental conditions. This experiment was carried out in three different nitrogen ranges (control, 120 kg N ha−1, and 300 kg N ha−1) + PK nutrient levels, with five replications used for leaf area measurement on seven different maize hybrids. Hybrids had different moisture, protein, oil, and starch contents. N (1, 2) + PK tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…KSC206, KSC704, KSC705 and KSC706 were identified as desirable single cross maize drought tolerant hybrids [ 139 ]. Szabó et al [ 114 ] studied the nutrient specific response of seven maize hybrids namely: SY Minerva, DKC4792, Sushi, Fornad, Loupiac, P0217 and Armagnac. Four early-maturing sweet maize hybrids: ‘Gyöngyhajnal’, ‘Nugát 72’, ‘Strongstar’ and ‘Sweetstar’ commonly grown by Hungarian maize farmers have been investigated for cold stress tolerance [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KSC206, KSC704, KSC705 and KSC706 were identified as desirable single cross maize drought tolerant hybrids [ 139 ]. Szabó et al [ 114 ] studied the nutrient specific response of seven maize hybrids namely: SY Minerva, DKC4792, Sushi, Fornad, Loupiac, P0217 and Armagnac. Four early-maturing sweet maize hybrids: ‘Gyöngyhajnal’, ‘Nugát 72’, ‘Strongstar’ and ‘Sweetstar’ commonly grown by Hungarian maize farmers have been investigated for cold stress tolerance [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crop water use efficiency depends on several factors, namely: water holding capacity (WHC), crop physiological characteristics, meteorological (climatic) conditions, genotype and agronomic practices [ 113 ]. Improvement of water use efficiency for maize can be achieved through application of nitrogenous fertilisers for areas that receive enough rainfall or irrigation [ 114 ]. Nutrient supply management improves water use efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Leaves are the main organs for photosynthesis and carbohydrate accumulation [ 30 ]. Leaf area index (LAI) is a key parameter for characterizing the structure and function of the canopy [ 31 ]. Previous studies also reported that high-yield maize populations have a higher leaf area index [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The LAI, defined as the total one-sided leaf area per unit of ground area, is a crucial factor in climatic, ecological, and agronomical studies [11,12]. It is essential to exactly estimate the LAI for accurate simulations of transpiration, dry matter, and biomass accumulation; therefore, it has a large influence on crop growth and yield [13,14].…”
Section: Introductionmentioning
confidence: 99%